Peran Financial Technologi dalam Membentuk Pola Manajemen Keuangan Generasi Z - liya Saputri (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2026)
Digital transformation has driven the development of financial technology (fintech) as a more efficient, inclusive, and technology-based financial service innovation. Generation Z, as digital natives, is the group most adaptable to the use of fintech in their daily financial activities. This study aims to analyze the role of fintech in shaping Generation Z's financial management patterns by integrating behavioral finance perspectives and the Theory of Planned Behavior. The method used is a qualitative approach through a literature review of various relevant scientific journals, books, and research reports. The study results indicate that fintech plays a role in increasing financial access and control through real-time transaction monitoring features, strengthening digital financial literacy through application-based education, and encouraging investment participation from an early age.